ANALISIS STANDAR NASIONAL PENDIDIKAN TINGGI: STUDI KASUS DI UIN ANTASARI BANJARMASIN - Jejen Musfah; Budi Mulia (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2020)
This study is to analyze the implementation of National Standard of Higher Education (Standar Nasional Perguruan Tinggi/SNPT) at Postgraduate Program of Islamic Education Department at UIN Antasari Banjarmasin, Kalimantan Selatan. This research uses a qualitative approach by collecting data through documentations, interviews, and observations. The technical data analysis is based on data collection, data reduction, data presentation, and drawing conclusions. The results showed that firstly, SNPT at Postgraduate Program of Islamic Education Departmen at UIN Antasari have not been properly met. Secondly, students have highly academic interest, but with low quality of graduate. Thirdly, research and writing’s skills are really satisfied. Fourthly, the Islamic Education Departmen hasn’t met the characteristics of good governance based institution with adequate facilities, good input and mature processes, and reliable education management. This study implies that Postgraduate Program of Islamic Education Departmen needs to advance learning facilities in the form of air conditioning and special rooms for lecturers, and to make learning evaluation. This Departmen needs to make strict selection and recrutment of students, and improvement of the learning process in order to produce good quality graduates. This Departmen has also to encourage the simultaneous research among lecturers.